2018
DOI: 10.1111/jfbc.12658
|View full text |Cite
|
Sign up to set email alerts
|

Selective antifungal activity of chitosan and sulfonated chitosan against postharvest fungus isolated from blueberry

Abstract: Two fungal isolates, F12‐20 and F3‐1, were collected from postharvest blueberry in China. By phylogenetic analysis with the nuclear ribosomal internal transcribed spacer region and morphological analyses, they were initially identified as Penicillium and Arthrinium sacchari (A. sacchari). The results showed that water‐soluble chitosan (WCS) and sulfonated chitosan (SCS) could significantly reduce the radial growth of fungal mycelia. The best concentrations were 0.25 and 16 g L–1 for WCS and 0.50 and 64 g L–1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The subgroup analysis here (Figure 2) showed that 1% chitosan was significantly effective for reduction of disease incidence against: gray mold (studies, 12; total cases, 1,473), (Feliziani et al., 2015; Feliziani, Santini, Landi, & Romanazzi, 2013; Gao, Zhu, & Zhang, 2013; Gramisci, Lutez, Lopes, & Sangorrína, 2018; Hajji, Younes, Affes, Boufi, & Nasri, 2018; Kanetis, Exarchou, Charalambous, & Goulas, 2017; Romanazzi, Feliziani, Santini, & Landi, 2013; Shao, Tu, Tu, & Tu, 2012; Zheng et al., 2017) (MD, −23.97; 95% CI, −32.25 to −15.68; I 2 , 77.0%; p < 0.00001), as highly effective in nine of these studies, (Feliziani et al., 2015; Gao et al., 2013; Gramisci et al., 2018; Hajji et al., 2018; Kanetis et al., 2017; Romanazzi et al., 2013; Shao et al., 2012; Zheng et al., 2017); blue/green molds caused by Penicillium spp. (studies, 16; total cases, 1,968) (Cháfer, Sánchez‐González, González‐Martínez, & Chiralt, 2012; El Guilli, Hamza, Clément, Ibriz, & Ait Barka, 2016; Feliziani et al., 2013; Gramisci et al., 2018; Kharchoufi et al., 2018; Liu, Sun, Xiu, Huang, & Zhou, 2018; Lu et al., 2014; Romanazzi et al., 2013; Shao et al., 2012; Shao et al., 2015; Shi, Wang, Lu, & Deng, 2018; Wang, Wu, Qin, & Meng, 2014; Xing, Xu, Che, Li, & Li, 2011; Zheng et al., 2017) (MD, −30.85; 95% CI, −41.91 to −19.79; I 2 , 90.0%; p < 0.00001), as highly effective in nine of these studies (El Guilli et al., 2016; Liu et al., 2018; Lu et al., 2014; Romanazzi et al., 2013; Shao et al., 2015; Shi et al., 2018; Xing et al., 2011; Zheng et al., 2017); Rhizopus rot (studies, five; total cases, 1,740) (Cia, Benato, Pascholati, & Garcia, 2010; Ramos‐García et al., 2012; Romanazzi et al., 2013; Xing et al., 2015) (MD, −28.80; 95% CI, −46.13...…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…The subgroup analysis here (Figure 2) showed that 1% chitosan was significantly effective for reduction of disease incidence against: gray mold (studies, 12; total cases, 1,473), (Feliziani et al., 2015; Feliziani, Santini, Landi, & Romanazzi, 2013; Gao, Zhu, & Zhang, 2013; Gramisci, Lutez, Lopes, & Sangorrína, 2018; Hajji, Younes, Affes, Boufi, & Nasri, 2018; Kanetis, Exarchou, Charalambous, & Goulas, 2017; Romanazzi, Feliziani, Santini, & Landi, 2013; Shao, Tu, Tu, & Tu, 2012; Zheng et al., 2017) (MD, −23.97; 95% CI, −32.25 to −15.68; I 2 , 77.0%; p < 0.00001), as highly effective in nine of these studies, (Feliziani et al., 2015; Gao et al., 2013; Gramisci et al., 2018; Hajji et al., 2018; Kanetis et al., 2017; Romanazzi et al., 2013; Shao et al., 2012; Zheng et al., 2017); blue/green molds caused by Penicillium spp. (studies, 16; total cases, 1,968) (Cháfer, Sánchez‐González, González‐Martínez, & Chiralt, 2012; El Guilli, Hamza, Clément, Ibriz, & Ait Barka, 2016; Feliziani et al., 2013; Gramisci et al., 2018; Kharchoufi et al., 2018; Liu, Sun, Xiu, Huang, & Zhou, 2018; Lu et al., 2014; Romanazzi et al., 2013; Shao et al., 2012; Shao et al., 2015; Shi, Wang, Lu, & Deng, 2018; Wang, Wu, Qin, & Meng, 2014; Xing, Xu, Che, Li, & Li, 2011; Zheng et al., 2017) (MD, −30.85; 95% CI, −41.91 to −19.79; I 2 , 90.0%; p < 0.00001), as highly effective in nine of these studies (El Guilli et al., 2016; Liu et al., 2018; Lu et al., 2014; Romanazzi et al., 2013; Shao et al., 2015; Shi et al., 2018; Xing et al., 2011; Zheng et al., 2017); Rhizopus rot (studies, five; total cases, 1,740) (Cia, Benato, Pascholati, & Garcia, 2010; Ramos‐García et al., 2012; Romanazzi et al., 2013; Xing et al., 2015) (MD, −28.80; 95% CI, −46.13...…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…Generally, chemical extraction of chitin and chitosan has several advantages over biological processes such as short processing time, high DDA of chitosan, complete removal of organic salts, and can be readily scaled up to industrial production (El Knidri et al, 2018). Therefore, chemical extraction has been widely used for the manufacturing of chitin and chitosan (de Queiroz Antonino et al, 2017;Benhabiles et al, 2013;Liu et al, 2018;Tokatlı & Demirdöven, 2018). Because of the non-toxic and biodegradable nature, chitosan has been employed intensively in various forms such as antimicrobial, antioxidant, anticancer, anti-inflammatory, coagulating, wound healing, and bio-adhesive agent (Antonino et al, 2017).…”
mentioning
confidence: 99%
“…In the study of Liu et al [ 32 ], sulfonated chitosan (SCS) was prepared by nucleophilic substitution of 1,3-propane sultone with chitosan. The antifungal activities of the derivative in vitro and in vivo were determined by using Botrytis cinerea and Arthrinium sacchari as targets.…”
Section: Structure Combination Strategy For Antimicrobial Chitosan Derivativesmentioning
confidence: 99%